Mechanical Properties of Magnesium Die Castings Produced Utilizing Process Scrap - Fajkiel A.; Dudek P.; Reguła T. (Archives of Foundry Engineering, 2014)
Magnesium alloys are one of the lightest of all the structural materials. Because of their excellent physical and mechanical properties the alloys have been used more and more often in various branches of industry. They are cast mainly (over 90%) on cold and hot chamber die casting machines. One of the byproducts of casting processes is process scrap which amounts to about 40 to 60% of the total weight of a casting. The process scrap incorporates all the elements of gating systems and fault castings. Proper management of the process scrap is one of the necessities in term of economic and environmental aspects.